2022
DOI: 10.1111/jgs.17920
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic and income disparities in COVID‐19 vaccination among Medicare beneficiaries

Abstract: Background Older adults have been disproportionately affected by the COVID‐19 pandemic. Despite the widespread availability and proved effectiveness of COVID‐19 vaccines, the issue of inequity in vaccine uptake in the United States is a potential concern among different populations. This study examined racial and ethnic and income disparities in COVID‐19 vaccination rate among Medicare beneficiaries. Methods Data from the Medicare Current Beneficiary Survey (MCBS) COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
2
9
1
Order By: Relevance
“…We found that among 1,500 Black/African American, Latino, and White low-income adults, only 25% were extremely willing to be vaccinated in early 2021, yet by late summer, roughly 70% of had been vaccinated. This is notably higher than the vaccination rate of 46.3% reported in April 2021 for older low-income adults in another study ( Cheng and Li, 2022 ), highlighting how quickly vaccine rollout was performed in the United States. While no significant differences were observed between low-income and non-low-income Black/African American and Latino adults, low-income White adults were substantially less willing to be vaccinated and less likely to be vaccinated by late summer, compared to non-low-income White adults.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…We found that among 1,500 Black/African American, Latino, and White low-income adults, only 25% were extremely willing to be vaccinated in early 2021, yet by late summer, roughly 70% of had been vaccinated. This is notably higher than the vaccination rate of 46.3% reported in April 2021 for older low-income adults in another study ( Cheng and Li, 2022 ), highlighting how quickly vaccine rollout was performed in the United States. While no significant differences were observed between low-income and non-low-income Black/African American and Latino adults, low-income White adults were substantially less willing to be vaccinated and less likely to be vaccinated by late summer, compared to non-low-income White adults.…”
Section: Discussionmentioning
confidence: 54%
“…Disparities in COVID-19 vaccination, as well as other COVID-19 prevention behaviors, exist between high- and lower-income individuals and communities in the United States. ( Brownstein et al, 2022 , Cheng and Li, 2022 , Wachira et al, 2022 ) Racial-ethnic disparities in vaccine willingness and uptake have also been observed. ( Pingali et al, 2021 , Nápoles et al, 2021 ) However, less is known about how income disparities and racial-ethnic disparities in COVID-19 vaccine willingness and uptake intersect.…”
Section: Introductionmentioning
confidence: 99%
“…22 23 In the context of the USA, black/ African American adults were less likely to report intent to vaccinate against COVID-19 than their white counterparts, partly due to mistrust of the medical establishment, racial injustice and harmful historical health policies such as the Tuskegee syphilis study. [24][25][26][27] Another study suggests socioeconomic privilege and political ideology play a role in racial disparity for COVID-19 vaccination. 28 More specifically, factors associated with COVID-19 vaccine disparities (CVD) identified were education, median income and political ideology, whereas other social determinants of health were not strongly correlated to CVD.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…This relationship arises from the likelihood that well-educated individuals can access credible health data, understand the benefits of vaccination, and consequently make informed health decisions. Additionally, economic disparities are reflected in vaccination rates, with economically marginalized groups potentially facing challenges in accessing vaccination sites, scheduling appointments, and obtaining time off for vaccination [ 12 ].…”
Section: Introductionmentioning
confidence: 99%